Myotonometry and extended field-of-view ultrasound imaging allow reliable quantification of patellar tendon stiffness and length at rest and during maximal load, whereas several restrictions exist for the Achilles tendon - Wegener, Florian; Ritterbusch, Arne; Saal, Christian; Baumgart, Christian; Hoppe, Matthias W. (Frontiers in Sports and Active Living, 2024)
Introduction: Stiffness and length are established tendon parameters in sports and medicine. Myotonometry and ultrasound imaging are frequently used methods for the quantification of stiffness and length, but further studies are needed to clarify their reliability, especially when used in maximally loaded tendons and by different experienced investigators. This study aimed to determine the intra- and interrater reliability of measurements of patellar tendon (PT) and Achilles tendon (AT) stiffness and length using the myotonometry method and the extended field-of-view ultrasound (EFOV-US) technique at rest and maximal load performed by different experienced investigators. Methods: Twenty-seven participants were examined on three different days by one experienced and one novice investigator. Primary outcomes were the intraclass correlation coefficient (ICC) and associated 95% confidence interval (95% CI), coefficient of variation (CV), standard error of the measurement (SEM), and minimal detectable change (MDC) across the measurement days and investigators. Results: For PT measurements at rest and at maximal load, the estimated ICCs for stiffness and length were ≥.867 and ≥.970, respectively, with 95% CIs ranging from poor (.306) to excellent (.973) and good (.897) to excellent (.999), respectively. The CV, SEM, and MDC for PT stiffness and length were ≤5.2% and ≤2.0%, ≤39.3 N/m and ≤0.9 mm, and ≤108.9 N/m and ≤2.6 mm, respectively. For AT measurements, some restrictions are evident for stiffness at rest and both parameters at maximal load. However, regarding AT length at rest, the estimated ICC was ≥.996, with an excellent 95% CI (.987-.999). The CV, SEM, and MDC for AT length at rest were 2.8%, ≤1.1 mm, and ≤2.9 mm, respectively. Conclusion: The estimated ICCs show good to excellent reliability for the myotonometry method and EFOV-US technique for measuring PT stiffness and length at rest and maximal load for experienced and novice investigators. However, some restrictions are evident for the AT, especially for measurements at maximal load.